Teknologi Low-Frequency Acoustic untuk Identifikasi Gas Hidrat Berdasarkan Perubahan Karakter Seismik di Perairan Laut Aru - M. Agung Sedayu; Henry M. Manik; Subarsyah Subarsyah (Universitas Syiah Kuala, 2021)
Gas hydrate is a type of hydrocarbon formed like crystals and is formed in the seabed sediment layer. Water temperature and pressure affected the area where gas hydrates are formed; gas hydrates are composed of gas and water elements. Gas hydrates have the potential as an alternative to current uses of oils and gasses. The identification of gas hydrates on the seabed can be detected using low-frequency acoustic, seismic technology. This research aims to identify the presence of gas hydrate in Aru Sea waters based on changes in the seismic character of the gas hydrate. The method used is seismic data processing with ProMAX software. This research uses seismic data for the 3.01 trajectory acquired by the Marine Geology Research and Development Center in 2016 in the Aru Sea. Based on the data processed, gas hydrate was detected on the 3.01 line with a depth of 5,925 meters. Gas hydrate indicator on the seabed is characterized by cutting stratigraphy, reversing its polarity, high amplitude, and shape following the seabed.